A fuzzy analytic hierarchy process-based analysis for prioritization of barriers to the adoption of eHealth in India. (September 2022) - Das, Dikhita; Sengar, Anita
Highlights: Barriers to the adoption of eHealth identified and categorized for India. AHP with Fuzzy logic approach used for prioritization of barriers. Managerial and practical implications for these barriers. Marketing barrier most critical barrier to the adoption of eHealth. Abstract: Introduction: eHealth is essential for revolutionising the health sector in India. eHealth enhances patient-centred healthcare by providing digital solutions to improve the quality of care, communication between doctors and patients; enhances the management of health data and integration of healthcare systems. Despite the importance of eHealth and the National Digital Health Mission in India, the adoption of eHealth faces several barriers. The objective of this research is to identify and classify the factors that act as barriers to the adoption of eHealth in India. Methodology: These barriers were ranked using a fuzzy analytic hierarchy process, which is a multi-criteria decision-making approach. Thirty-seven barriers were identified and grouped into eight categories named customer, regulatory, technical, organizational, practitioner, marketing, administrative, and economic. Results: The barriers under the marketing category are the most significant obstacles to the deployment of eHealth in India, which includes promotion, customer engagement, and customer loyalty. Customer-related barriers were identified as the second most important barriers to eHealth, which included health consciousness, literacy in eHealth, lack of motivational value for elderly people, unclear benefits, learning new technology, lack of trust, and less knowledge of health experts, and cultural ethical challenges. Following these, the other barrier categories were administrative, organizational, regulatory, and practitioner-related. The economic barrier was identified to be the least important among all the barrier categories. Conclusion: This is among the first studies to look into the reported impediments to eHealth adoption in India in-depth and categorize and prioritize them. This study contributes to our understanding of eHealth obstacle identification, categorization, and prioritisation, and explains why, even though eHealth was first described in India in 2005 and globally in 1999, there are still barriers to eHealth adoption in India.